2015
DOI: 10.1159/000369708
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Mitigate Cirrhosis through BMP7

Abstract: Background/Aims: Transplantation of mesenchymal stem cells (MSCs) has therapeutic effects on various diseases, while its effect on developing cirrhosis as well as the underlying mechanism remained largely unknown. Methods: Twenty C57BL/6 mice were randomly separated into 2 groups of ten each. One group received transplantation of MSCs, while the other group received saline as control. The mice then received intraperitoneal injection of carbon tetrachloride (CCl4) twice per week for 8 weeks to develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Mesenchymal stem cells (MSCs) have been initially identified in the bone marrow, and are the stem-like cells that expand in culture and may differentiate into osteoblasts, chondrocytes, and adipocytes [8][9][10][11][12][13][14]. Clinical data provide evidence to demonstrate a therapeutic effect of transplantation of MSCs in some diseases, including ALI, in which MSCs promote tissue repair through various mechanisms [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesenchymal stem cells (MSCs) have been initially identified in the bone marrow, and are the stem-like cells that expand in culture and may differentiate into osteoblasts, chondrocytes, and adipocytes [8][9][10][11][12][13][14]. Clinical data provide evidence to demonstrate a therapeutic effect of transplantation of MSCs in some diseases, including ALI, in which MSCs promote tissue repair through various mechanisms [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical data provide evidence to demonstrate a therapeutic effect of transplantation of MSCs in some diseases, including ALI, in which MSCs promote tissue repair through various mechanisms [9][10][11][12][13][14]. When MSCs are intravenously delivered, they are mainly localized in the lungs, as a privilege for them to be used for treating lung diseases [15].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the potential effects on tissue repair, transplantation of bone-marrow-derived mesenchymal stem cells (MSCs) has been used in treating a variety of diseases [1-3], including spinal cord injury (SCI), in which the neural cell regeneration was compensated by MSC grafting [4-6]. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, MSCs have been shown to have significant therapeutic effects on a variety of diseases, since mesenchymal cells play a critical role in tissue repair and organ remodeling. For example, Li et al showed that transplantation of MSCs mitigates the severity of cirrhosis by secreting BMP7 to contradict the fibrogenic effects of transforming growth factor beta 1 (TGF-beta1) in the injured liver [5]. In another elegant study, transplantation of mesenchymal stem cells (MSCs) alleviated dextran sulfate sodium -induced colitis through their crosstalk with macrophages via TGF-beta receptor signaling [4].…”
Section: Introductionmentioning
confidence: 99%